Automatic Monitoring and Controlling System for Hydroponics Greenhouse Environments Through Smartphone Application - Channumsin, Orapin; Trancharoen, Jirasin; Sonchaiyaphum, Sarut; Pimpol, Jirapun; Tangsrirat, Worapong (My University, 2022)
This article proposes the design and construction of environmental control systems for hydroponics grown vegetables that enable automated control over the environment inside the greenhouse to be most suitable for the plants growth by using microcontroller processing. The systems can track various measurements such as temperature, humidity, intensity of light, water pH value, and water level in a greenhouse by using Blynk application on a smartphone as well as LCD display screen surrounding the greenhouse area. In addition, the systems can automatically control the operation of ventilation fans and mist sprayer machine according to the specified humidity temperature value and it can be set ON and OFF timer for whirlpool pump and LED light bulbs. Moreover, after a 42-day-Testing period of planting three varieties of lettuce, which are Red Oak, Green Oak, and Frillice Iceberg Lettuces, it has been found that Red Oak lettuces have an average width of 21.2 cm, a length of 26.4 cm with a weight of 120 gram, while Green Oak lettuces have an average width of 8.1 cm., a length of 31.0 cm with a weight of 120 gram and lastly, Frillice Iceberg Lettuce has an average width of 19.0 cm, a length of 46.9 cm and a weight of 200 gram.
Keywords: Blynk application; environmental control system; hydroponics greenhouse